On two new species of arboreal crabs from phytotelms in Sarawak, Borneo (Crustacea: Brachyura: Gecarcinucidae: Arachnothelphusa) - Ng, Peter K. L. (Zootaxa, 2021)
Two new species of the gecarcinucid freshwater crab genus Arachnothelphusa are described from the Malaysian state of Sarawak in Borneo; one from Lanjak-Entimau Wildlife Sanctuary and another from Bako National Park. Arachnothelphusa rimba n. sp. is distinctive in possessing very long legs and a male first gonopod which has a cylindrical proximal part of the terminal segment, with the distal part sharply tapering to an acute tip. Arachnothelphusa bako n. sp. is superficially closest to A. kadamaiana from Sabah, but differs markedly by its narrower epistome, and proportionately shorter third maxillipeds and ambulatory legs.